Occurrence of primarily noninducible atrioventricular nodal reentry tachycardia after radiofrequency delivery in the slow pathway region during empirical slow pathway modulation. Issue 11 (22nd November 2017) - Wegner, Felix Konrad; Bögeholz, Nils; Leitz, Patrick; Frommeyer, Gerrit; Dechering, Dirk Georg; Kochhäuser, Simon; Lange, Philipp Sebastian; Köbe, Julia; Wasmer, Kristina; Mönnig, Gerold; Eckardt, Lars; Pott, Christian
Abstract : Background: The first‐line therapy for atrioventricular nodal reentry tachycardia (AVNRT) is catheter‐based slow pathway modulation. If AVNRT is not inducible during an electrophysiological study, an empirical slow pathway modulation (ESPM) may be considered in patients with dual atrioventricular nodal physiology and/or a typical electrocardiogram (ECG). Methods: We screened 149 symptomatic patients who underwent ESPM in our department between 1993 and 2013. All patients fulfilled the following criteria: (1) either dual atrioventricular nodal (AVN) physiology with up to 2 AVN echo beats or characteristic ECG documentation or both, (2) noninducibility of AVNRT by programmed stimulation, and (3) completion of a telephone questionnaire for long‐term follow‐up. Out of this population we retrospectively investigated 13 patients who were primarily noninducible but in whom an AVNRT occurred during or after radiofrequency (RF) delivery. Results: When AVNRT occurred, the procedure lost its empirical character, and RF delivery was continued until the procedural endpoint of noninducibility of AVNRT. This endpoint was reached in all but one patient (92%). After a follow‐up of 73 ± 15 months, this patient was the only one who reported no benefit from the procedure. Conclusions: Out of 149 initially noninducible patients, a considerable number (9%) exhibited AVNRT during or after RF delivery. These patients crossed over from empirical to controlled slow pathway modulation resulting in a good clinical outcome. Our observations should encourage electrophysiologists to repeat programmed stimulation even after initial empirical RF delivery to retest for inducibility.